Examining the Effect of Cuff Pressure in Blood Flow Restriction Training - KOCAMAN, Hüsnü; AYDOS, Latif (International Journal of Holistic Health, Sports and Recreation, 2023)
Blood flow restriction training, which is one of the methods applied to enhance muscle hypertrophy and strength, has gained popularity in light of the findings revealed by recent scientific research. It is an undeniable fact that high-intensity resistance exercises contribute to an increase in muscle hypertrophy and strength. However, it has been observed that these exercises also elevate the risk of injury due to their high intensity. On the other hand, low-intensity resistance exercises do not provide sufficient mechanical tension and metabolic accumulation necessary for the development of muscle strength and hypertrophy. At this point, low-intensity blood flow restriction resistance exercises can minimize the potential risks of high-intensity exercises. The reduction in venous circulation caused by the restriction leads to an increased impact of metabolic accumulation on muscle hypertrophy. As the prevalence of blood flow restriction resistance exercises increases, inconsistencies arise in the recommended levels of cuff pressures measured in mmHg. This brief compilation aims to present a concise overview of the literature, explaining the principles of blood flow restriction training and providing insights into determining the cuff pressures used during the application. Initial research on blood flow restriction employed fixed pressures, but with advancements in technology, contemporary studies demonstrate diverse outcomes by applying individualized cuff pressures based on factors such as soft tissue volume, body fat percentage, and limb circumference. Cuff pressures vary between 50-300 mm Hg depending on individual differences. These individual differences should be considered for achieving the desired results.